2003
DOI: 10.1074/jbc.m307234200
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Modulation of Rho GTPases during in Vitro Formation of Capillary Vascular Network

Abstract: Endothelial cells (ECs) self-organize into capillary networks when plated on extracellular matrix. In this process, Rho GTPases-mediated cytoskeletal dynamics control cell movement and organization of cell-to-matrix and cell-to-cell contacts. Time course analysis of RhoA and Rac1 activation matches specific morphological aspects of nascent pattern. RhoA-GTP increases early during EC adhesion and accumulates at sites of membrane ruffling. Rac1 is activated later and localizes in lamellipodia and at cell-to-cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 65 publications
4
43
2
Order By: Relevance
“…Finally, consistent with our experiments implicating Rho and Rho kinase critically in EC contraction of collagen I gels (Fig. 3B), others have reported that both N19RhoA and Y-27632 (5 M) suppressed EC contraction of three-dimensional Matrigel (31).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Finally, consistent with our experiments implicating Rho and Rho kinase critically in EC contraction of collagen I gels (Fig. 3B), others have reported that both N19RhoA and Y-27632 (5 M) suppressed EC contraction of three-dimensional Matrigel (31).…”
Section: Resultssupporting
confidence: 80%
“…We observed no significant differences in EC density between the N19RhoA and V14RhoA groups; however, differences in cross-sectional area of blood vessel lumens were highly significant (P Ͻ 0.001). In addition, others have reported that transduction with N19RhoA suppressed EC motility (31), but it appears that they achieved considerably greater inhibition of Rho activity (Ϸ75%) in comparison with that achieved in our experiments (Ϸ20%). Thus, the consequences of modulating Rho activity for EC migration may depend critically on percent change in Rho activity.…”
Section: Resultscontrasting
confidence: 46%
“…These include fibroblast motility during wound repair and endothelial metamorphosis during angiogenesis (Cascone et al, 2003;Harms et al, 2005). The FAK-␤PIX-Rac1 pathway that is defined in this work may be a critical determinant of success in these endeavors by providing the targeting and assembly of Rac1-containing molecular networks at focal complex and focal adhesion sites.…”
Section: Discussionmentioning
confidence: 99%
“…Rac1, a major member of the Rho GTPase family, is related to tumorigenesis [153], invasion and metastasis [154], and angiogenesis [81,155]. Xue et al showed that VEGF and HIF-1α were down-regulated in gastric cancer cells which were transfected with a Rac1 siRNA expression vector [156].…”
Section: Anti-angiogenesismentioning
confidence: 99%